AFFECT ANALYSIS OF CRIME NEWS IN THE JAKARTA POST AND THE JAKARTA GLOBE: A STUDY OF SYSTEMIC FUNCTIONAL LINGUISTICS - Dien Novita; Eva Tuckyta Sari Sujatna (Universitas Padjadjaran, 2019)
This study explores the affect of appraisal systems by comparing the crime news in The Jakarta Post and The Jakarta Globe. There were six texts of the crime news that were classified into the same topics. These texts were analysed using Appraisal Systems Theory (Martin & White, 2005). The objectives of the present study are to find out the differences of the affect of crime news in The Jakarta Post and The Jakarta Globe and then to know the types of appraising items in The Jakarta Post and The Jakarta Globe. The data is analysed by using the mixed method research. The present writer found out that the writers in The Jakarta Globe present the affect dominantly. The Jakarta Globe shows 63,8% of affect and it is dominated by the affect of dis/satisfaction. However, The Jakarta Post shows 36,2% of affect and it is dominated by the affect of in/security. In addition, the types of appraising items that occur in the affect of crime news are mental process, behavioural process, relational process, attitudinal lexis, minor clause, epithet and grammatical item.